Automatic Suppression Reduces Anxiety-Related Overestimation of Time Perception - Yuan, Jiajin; Li, Lingjing; Tian, Yu (Frontiers in Physiology, 2020)
Anxiety has been found to lengthen time perception, especially the time perception of negative stimuli. This anxiety-related time overestimation is thought to be mainly associated with massively increased arousal. Suppression, which can be achieved either deliberately or automatically, has been demonstrated to be effective in reducing arousal. Consequently, the present study explored the effectiveness of both deliberate suppression (Experiment 1) and automatic suppression (Experiment 2) in reducing the time distortion in anxiety. A temporal bisection task (TBT), featuring negative and neutral pictures, was used to measure time perception, while the self-reported arousal was used to assess arousal. The deliberate suppression was manipulated by asking participants to suppress their emotional expressions; while automatic suppression was manipulated through a sentence-unscrambling task featuring suppression-related words, which can unconsciously prime suppression. The results of Experiment 1 showed that deliberate suppression did not reduce the anxiety-related time overestimation and arousal. However, Experiment 2 showed that automatic suppression significantly reduced the anxiety-related time overestimation, with significant arousal reduction being observed. In conclusion, automatic suppression, but not deliberate suppression, is effective for reducing the effect of anxiety on time perception.